2014
DOI: 10.21512/humaniora.v5i2.3179
|View full text |Cite
|
Sign up to set email alerts
|

Error Made in Conversation by Indonesian Learners Learning English Based on Syntax and Exchanging Information

Abstract: In learning a second language or foreign language (L2),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In short, the finding on the most frequent error produced by students corroborate to the most previous studies that omission was the highest error made (Wiannastiti, 2014;Saad & Salwameh, 2014;Simbolon, 2015;Safrida & Kasim, 2016;Herlina, 2017;Chania & Amri, 2019;Viandari, 2019;Kamlasi, 2019;Karisma & Bulan, 2022;Prawiti et al, 2022;and Sahan et al, 2023). Meanwhile, this study is in contrast with Ruminar (2018) that she figured out misformation as the highest.…”
Section: E14supporting
confidence: 87%
See 1 more Smart Citation
“…In short, the finding on the most frequent error produced by students corroborate to the most previous studies that omission was the highest error made (Wiannastiti, 2014;Saad & Salwameh, 2014;Simbolon, 2015;Safrida & Kasim, 2016;Herlina, 2017;Chania & Amri, 2019;Viandari, 2019;Kamlasi, 2019;Karisma & Bulan, 2022;Prawiti et al, 2022;and Sahan et al, 2023). Meanwhile, this study is in contrast with Ruminar (2018) that she figured out misformation as the highest.…”
Section: E14supporting
confidence: 87%
“…Dealing with the study of error analysis and the sources, there have been a number of scholars concerning on studies attempting to analyze the learners' errors by employing surface strategy taxonomy in spoken production, including Wiannastiti (2014), Saad and Salwameh (2014), Simbolon (2015), Safrida and Kasim (2016), Herlina (2017), Chania and Amri (2019), Viandari (2019), Kamlasi (2019), Karisma and Bulan (2022), Prawiti et al (2022), and Sahan et al (2023. These studies looked at the errors produced by students when speaking and the causes of the problems.…”
Section: Introductionmentioning
confidence: 99%
“…This study proved that some differences of phonemic and phonetic features between English and Indonesian make 20 English Department students of Tadulako University, Indonesia, as the respondents, still have problems in pronouncing English words. Another study on syntax errors made by L2 learners in conversation was conducted by Wiannastiti (2014). This study revealed that L2 learners made some errors in grammar and exchanging information because they are influenced by L1.…”
Section: B Previous Studiesmentioning
confidence: 99%
“…In the context of Indonesia, most studies on Indonesian EFL learner language have been more on the errors that the learners produce, rather than the performances that learners make (e.g. Hidayati, 2011;Septiana, 2011;Fadzilyna, 2013;Wiannastiti, 2014). In contrast, not many studies have been conducted to investigate Indonesian learners' language in terms of their ability to perform in the second language (Widyastuti, 2015).…”
Section: Introductionmentioning
confidence: 99%